IMPLEMENTASI KEBIJAKAN PENDIDIKAN DALAM PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Andini; Farid Setiawan; Fita Triyana; Khalidah Fitri Arum Sari (JURNAL PUSAKA, 2021)
The development of Islamic religious education is very important considering that there are still many unresolved educational problems regarding morals. Educational policies also contribute to the development of Islamic religious education. This study aims to determine the implementation of educational policies in terms of the development of Islamic education in schools. Research on educational policies in the development of Islamic education in schools is conducted by reviewing the manual literature. Islamic education policies are very dependent on national policy, thus experts must contribute in formulating the policies that are in line with community expectations regarding to the growth of moral maturity and characters.